Children in sport and exercise: Bioenergetics and anaerobic exercise - Armstrong, N.; Welsman, J. (British Journal of Physical Education, 1997)
The presence of the three energy systems in an individual is genetically determined. The types of muscle fibers that exist in a person is relatively stable from six years on and so energy producing capacities are established very early in young children. Anaerobic Function Muscular concentration of ATP is similar in children, adolescents, and adults although CP concentration may be lower in children. The total reservoir of high energy phosphates is lower in children because of their smaller muscle mass relative to structure. In exercise, depletion of high-energy phosphates occurs at similar rates for children and adults. Children and adolescents have significantly lower muscle glycogen stores than adults and also are less capable of generating ATP by glycogenloysis. Young people do not have the same capabilities as adults to perform strenuous exercise for periods between 10 and 60 seconds. Boys' anaerobic performance increases with age from childhood to adulthood. When related to body mass, the anaerobic performance of an 8 year-old boy is about 70% of an 11 year-old. Girls' anaerobic performance also increases from childhood but appears to reach a maximum value during the teen years. Gender-related differences are minimal prior to puberty. However, during adolescence boys become significantly better anaerobic performers than girls, an advantage that is retained for the remaining years.